Three-Dimensional CFD study of a Candle Ceramic Filter - Jolius, Gimbun; Ili Izyan Safuraa, Abdul Karim; Luqman Chuah, Abdullah (Penerbit UMP, 2009)
Tightened environmental legislation enacted as a consequence of government policy has compelled industry to pay serious attention to air pollution issues. Gas cleaning with ceramic filters has proven to be the most important technology for removal of particulate emissions at high temperatures. This paper presents a computational fluid dynamics (CFD) investigation of a rigid candle ceramic filter. The aim is to examine numerically the pressure drop and velocity profile along the candle filter under a filtration mode. The filter element was modeled as a porous medium and the media resistance at x, y and z direction is assumed to be isotropic. The gas flow within the porous media (filter element) is also assumed to be a laminar flow. The CFD calculations show a good agreement with the experimental data, with an average discrepancy around 5%, which probably in the same magnitude of the experimental error. The modeling exercise presented in this study offers an alternative solution for examining a pressure drop in ceramic filter via computational method and may be useful in design of a ceramic filter.